PERAN BPR SYARIAH TERHADAP PERTUMBUHAN EKONOMI DAERAH MELALUI KETAHANAN PANGAN: DAMPAK MODERASI INFLASI PANGAN DI DAERAH ISTIMEWA YOGYAKARTA - Evi Sistiyarini; Ririn Poerwanti; Titis Puspitaningrum Dewi Kartika (Journal of Financial Economics & Investment, 2025)
This study examines the role of Islamic rural banks in promoting regional economic growth in the Special Region of Yogyakarta (DIY), with food inflation as a moderating variable. Using secondary data, a purposive sample of 10 Islamic Rural Banks (BPR Syariah) was analyzed. The variables include Financing to Deposit Ratio (FDR) (X1), Non-Performing Financing (NPF) (X2), bank size (X3), Farmers’ Terms of Trade (NTP) (X4), food inflation (Z), and economic growth measured by Gross Regional Domestic Product (GRDP) (Y). Moderated Regression Analysis (MRA) was employed. Before moderation, NTP (X4) had a significant positive effect on economic growth, while FDR (X1), NPF (X2), and bank size (X3) showed positive but insignificant effects. Food inflation had a positive but insignificant effect as a moderator. After moderation, FDR (X1) and bank size (X3) remained positive but insignificant, while NPF (X2), NTP (X4), and food inflation had significant positive effects on economic growth. Food inflation did not moderate the effect of FDR (X1) but significantly and negatively moderated the effect of NTP (X4) on economic growth. These findings highlight the nuanced role of Islamic rural banks and macroeconomic variables in regional economic development.